Hybrid forums, knowledge deficits and the multiple uncertainties of resource extraction: Negotiating the local governance of shale gas in Poland. (June 2017) - Lis, Aleksandra; Stasik, Agata Kinga
Abstract: The paper examines shale gas development as a situation of resource exploration loaded with multiple uncertainties stemming not only from technology-generated unknowns but mainly from the unknowns about the volume of exploitable resource and about the ways in which shale gas industry will exist 'locally'. By examining first information meetings organized by NGOs, companies and local authorities in Poland: Przywidz, Mikołajki Pomorskie and Żurawlów, the paper shows that uncertainty is built around three dimensions that are to be shared by communities and companies if exploration takes place: knowledge, space and time. Discussions around these three issues reveal knowledge deficits on all sides, contributing to the emergence of new areas of uncertainty and making any agreement difficult. By referring to the concept of 'hybrid forums', the analysis also shows how a gathering that is initially framed by the organizers as an 'information meeting' transforms into a 'hybrid forum' where new facts, values and identities emerge due to the confrontation of perspectives represented by heterogeneous stakeholders.